Disability assessment of diabetic patients in Erbil city - Al-Banna, Dara Abdulla; Khuder, Saadia Ahmed (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and objectives: The disabling effects of diabetes mellitus are multi-factorial, which can result in the high prevalence of long term complications. The aim of this study was to assess disability levels of diabetic patients.Methods: A quantitative design descriptive study was conducted in Leila Qasim Center in Erbil City in the Kurdistan Region of Iraq from February 2012 to February 2013. A non-probability purposive sample of 400 diabetic patients for more than 5 years was selected. A questionnaire was designed and divided into three parts: sociodemographic data, clinical data, and the standardized questionnaire developed by World Health Organization for disability assessment.Results: The highest percentage (57%) of diabetic patients had a moderate level of disability, while 23% had a mild level of disability. Severe level of disability was present in 20% of sample. No one had not disability or extreme level of disability.Conclusion: More than half of diabetic patients were in the moderate level of disability.